EFEK HIPOTERMIA SEBAGAI NEUROPROTEKTIF PADA STROKE ISKEMIK - Chandra Wirawan* Shierly** (Neurona Majalah Kedokteran Neuro Sains, 2020)
INCIDENCE OF STROKE HAS BEEN INCREASING CONTINUOUSLY IT IS FOUND THAT A HIGHER PREVALENCE OF ISCHEMIC STROKE THAN THE PREVALENCE OF HEMORRHAGIC STROKE AND THE DISABILITY OF STROKE IS THE HIGHEST OF ALL OTHER DISEASES MANY METHODS OF THERAPEUTIC HYPOTHERMIA CAN BE DONE LOCALLY IN BODY SURFACE OR LESION AND SYSTEMICALLY ENDOVASCULAR